Coordination and Crosstalk between Autophagosome and Multivesicular Body Pathways in Plant Stress Responses - Mengxue Wang; Xifeng Li; Shuwei Luo; Baofang Fan; Cheng Zhu; Zhixiang Chen (Cells, 2020)
In eukaryotic cells, autophagosomes and multivesicular bodies (MVBs) are two closely related partners in the lysosomal/vacuolar protein degradation system. Autophagosomes are double membrane-bound organelles that transport cytoplasmic components, including proteins and organelles for autophagic degradation in the lysosomes/vacuoles. MVBs are single-membrane organelles in the endocytic pathway that contain intraluminal vesicles whose content is either degraded in the lysosomes/vacuoles or recycled to the cell surface. In plants, both autophagosome and MVB pathways play important roles in plant responses to biotic and abiotic stresses. More recent studies have revealed that autophagosomes and MVBs also act together in plant stress responses in a variety of processes, including deployment of defense-related molecules, regulation of cell death, trafficking and degradation of membrane and soluble constituents, and modulation of plant hormone metabolism and signaling. In this review, we discuss these recent findings on the coordination and crosstalk between autophagosome and MVB pathways that contribute to the complex network of plant stress responses.